ANALISIS PENGARUH QUALITY OF WORK LIFE, MOTIVASI BERPRESTASI DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA GURU - Hersanti, Dessi Wahyu; -, Gunistiyo; Rahmatika, Dien Noviany (Jurnal Inovasi Pembelajaran Karakter, 2020)
The purpose of this research is to find out 1) The effect of the Quality of Work Life of Teachers on organizational commitment, 2) The effect of achievement motivation on organizational commitment, 3) The effect of the principal transformational leadership on teacher commitment, 4) The effect of Quality of Work Life on teacher performance, 5) The influence of achievement motivation on teacher performance, 6) The influence of principals' transformational leadership on teacher performance, 7) The effect of organizational commitment affects teacher performance 8) Significance of organizational commitment in mediating the effect of Quality of Work Life (QWL) on teacher performance, 9) . The significance of organizational commitment in mediating the effect of achievement motivation on teacher performance, 10). The significance of organizational commitment in mediating the effects of transformational leadership on teacher performance. Respondents in this study were 77 people. The respondents were all civil servant teachers (PNS) in state junior high schools throughout the Larangan District. The data needed is collected by questionnaire technique. Analysis of the data used in this research is descriptive statistics and statistical analysis. From the research results it can be concluded that 1) Quality of work life influences organizational commitment, 2) Achievement motivation does not affect organizational commitment, 3) Transformational leadership influences towards organizational commitment, 4) Quality of work life influences teacher performance, 5 ) Achievement motivation has no effect on teacher performance. 6). Transformational leadership affects the performance of teachers. 7). Organizational commitment influences teacher performance. 8). Organizational commitment is able to mediate the effect of quality of work life on teacher performance. 9). Organizational commitment is not able to mediate the effect of achievement motivation on teacher performance. 10). Organizational commitment is able to mediate the influence of transformational leadership on teacher performance.